Student Subjectivity in the Marketised University - Bunn, Geoff; Langer, Susanne; Fellows, Nina K. (Frontiers in Psychology, 2022)
We present data from an exploratory qualitative interview-based pedagogical research project on the development of student agency in higher education. Our aim was to respond to Nick Zepke’s claim that what is often missing from the current neoliberal discourse of higher education ‘is students having a voice in what and how they learn and how they can action their voice in the wider community as agentic citizens.’ Informed by Lacanian discourse analysis, our project investigated the opportunities and threats facing some of our undergraduate students as they struggled to exercise agency and develop autonomy in the marketised university. Repeat interviews (n = 15) with final year students focussed on the psychosocial categories of power, affect, intersubjectivity and desire. The analysis was guided by Lacan’s theory of the four discourses, an account of the vicissitudes of agency. We found that students can move between discourses depending on the extent to which their agency (operationalised here as Lacan’s ‘object cause of desire,’ the objet petit a) was enabled or thwarted. Our critique of the metaphor of the ‘student journey’ addresses the implications for learning and teaching and the university’s mission to develop its students in light of perceived commercial pressures.